Optimizing UPLC isocyanate determination through a Taguchi experimental design approach. (25th March 2013) - André, Catarina; Jorge, Fabiana; Castanheira, Isabel; Matos, Ana
Abstract : The development of a chromatographic procedure for an ultra‐performance liquid chromatography can be a very time‐consuming task, as the general approach for finding the appropriate operating conditions has been a trial‐and‐error process. The present study reports a novel approach in the field of ultra‐performance liquid chromatography by using statistical experimental design based on Taguchi's method, which allows a complete separation of nine isocyanates present in a complex matrix. The resolution between two adjacent peaks was considered as a quality characteristic and transformed to a Taguchi signal‐to‐noise ratio. An orthogonal array L9 (3 4 ) was selected to analyze the effect of four chromatographic factors, that is, proportion of solvent, percent triethylamine (v/v), temperature (°C), and flow (mL min −1 ), with three levels each. The joint analysis performed to the significant factors achieved in the eight analyses of variance allowed to identify two methods to conduct a complete separation of all peaks. Six isocyanates were separated with the first method, with all factors at the lowest level. The remaining three isocyanates were separated with the second method, with the proportion of solvent at the highest level and the other factors at the lowest level. The overall Taguchi experimental design identified the proportion of solvent and the flow rate as major chromatographic factors. Finally, confirmatory experiments were performed with samples prepared with six and three isocyanates, confirming the complete separation of all isocyanates in the study. The Taguchi methods provided a systematic and efficient methodology for this optimization, with considerably less effort than would be required for other optimizations techniques. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : A novel approach in the field of UPLC by using experimental design based on Taguchi's method was used to obtain a complete separation of nine isocyanates present in a complex matrix. An orthogonal array L9 (3 4 ) was selected, considering four chromatographic factors, with three levels each (proportion of solvent, %TEA (v/v), temperature (°C), and flow (mL min −1 )). The resolution between two adjacent peaks was considered as a quality characteristic. The use of Taguchi methods allowed to identify two methods to conduct a complete separation of all peaks.